The relation of entrepreneur cognition and personality: the determinant factors of e-commerce entrepreneurship involvement in Malaysia - Ahmad Firdause, Md Fadzil; Puspa Liza, Ghazali; Mohd Rafi, Yaacob; Mohd Nazri, Muhayiddin (2018)
A number of researches on entrepreneurs have been intensively conducted for the past years considering that it is one of the important elements in business. An entrepreneur is responsible for every aspect of new ventures creation considering that they are the lead person in every business decision. The process of forming new ventures is very challenging and involves a lot of thought. The process of forming new ventures has only received little attention in most established studies investigating the cognitive aspects of entrepreneur. On top of that, researchers tend to ignore the issues related to quality of entrepreneur in the creation of e-commerce ventures. Much uncertainty still exists; hence, this study set out to determine the role of entrepreneurial cognitive and personality that acts as the crucial components in the creation of new e-commerce ventures in Malaysia. This research uses a case studies approach in which data was collected by interviewing a total of twelve e-commerce entrepreneurs from May 2013 until December 2014. The findings revealed that personal background (education and family) as well as work and business skills are the important factors in the creation of new ventures by cognitive entrepreneurs in Malaysia. In the case of entrepreneur personalities; seven types of personality such as creativity, risk taking, inspiration, need for autonomy and freedom, tolerance of ambiguity, hardworking and persistence, and optimistic have vigorously to contributing of new e-commerce venture creation in Malaysia. Therefore, it is best for the government to promote entrepreneurial activity in the country by highlighting the elements of entrepreneurs in terms of cognitive ability and personality aspects. Finally, the emergence of new ventures is hoped to further strengthen the economic progress of the country.